When the Exit?: The Difficult Politics of German Coal. Issue 1 (1st March 2019) - Coggio, Tessa; Gustafson, Thane
Abstract : This article considers Germany's contentious exit from brown coal (lignite), now set for 2038. While greener alternatives, such as wind, solar, or natural gas have been reducing coal's standing in Germany's energy mix for years, coal proponents, backed by special interests, have pushed back at all levels of government. With a focus on the politics of coal during the 2017 parliamentary elections, the tedious months of coalition negotiations and the work of the coal committee since summer 2018, we explore how policymakers try to reconcile competing interests at the federal state, local, as well as international levels.